Small Talk - Hui-chen, Huang (Taiwan, 2016)
A Taiwanese filmmaker shares a flat with her mother, but for decades, they have treated each other like strangers. Their only exchanges are the meals the mother cooks and leaves for her daughter on the dining room table. Silence permeates the house, beneath which lies a heavy secret that suffocates the mother and prevents her from speaking. One day, the filmmaker summons up her courage and starts the conversation that will transform their relationship. The camera becomes a gateway and tool to pry open the Pandora’s box, and reveal the long-concealed secrets. Are they ready to face what’s been buried for so long?
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films